2015
DOI: 10.1097/aog.0000000000000694
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Growth, Cognitive Function, and Brain Volumes in Childhood and Adolescence

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…(2) The low body weight in the animals with MIUH did not normalize until reaching young adulthood, which is commonly observed in patients with IUGR24. (3) MIUH resulted in lower brain weights and decreased cortex and white matter areas, which are common features observed via magnetic resonance imaging (MRI) in patients with IUGR2526. (4) Lateral ventricular enlargement was also observed in the present model and is also frequently found in patients with IUGR and VLBW27.…”
Section: Discussionsupporting
confidence: 60%
“…(2) The low body weight in the animals with MIUH did not normalize until reaching young adulthood, which is commonly observed in patients with IUGR24. (3) MIUH resulted in lower brain weights and decreased cortex and white matter areas, which are common features observed via magnetic resonance imaging (MRI) in patients with IUGR2526. (4) Lateral ventricular enlargement was also observed in the present model and is also frequently found in patients with IUGR and VLBW27.…”
Section: Discussionsupporting
confidence: 60%
“…The group of Martinussen et al conducted MRI studies in 15-year old boys and girls: A first study showed reduced brain volume in those born SGA compared to controls and a second study demonstrated smaller brains and proportionally smaller regional brain volumes, while hippocampus volume was a significant predictor of cognitive function (Martinussen et al, 2005;Martinussen et al, 2009). In a third study, they again showed smaller brain volumes in 15-year olds born SGA, but these findings were only present in those with fetal growth restriction as evidenced by frequent ultrasounds in pregnancy (Rogne et al, 2015). An additional study, performed at age 20 years, showed regional reductions in cortical surface area and total brain volume, cortical GM, cerebral WM and putamen volumes were reduced (Ostgard et al, 2014).…”
Section: Neuroimaging Studies Revealing Neuroanatomical Differences Amentioning
confidence: 85%
“…Such studies have made important contributions to our understanding of potential drug effects, pointing out plausible biological causal relationships. 49 However, the translational potential of animal research is always limited by interspecies differences. Lack of pharmacokinetic reference data in animals is an important limitation, 86 and animal models have limited ability to elucidate complex aspects of human development.…”
Section: Methodological Challenges In Clinical Studies Exploring Prenmentioning
confidence: 99%
“…Reduced brain volumes have been reported in children born prematurely/with low birth weight and in term-born children with intrauterine growth restriction [48,49]. Even in healthy term-born children, an association between birth weight and morphometric brain characteristics has been shown [36].…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation